2001
DOI: 10.1002/cne.1335
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related decline of presumptive inhibitory synapses in the sensorimotor cortex as revealed by the physical disector

Abstract: The synapse, as the site of functional neural interaction, has been suggested as a possible substrate for age-related impairment of cognitive ability. Using the physical disector probe with tissue prepared for ultrastructural analysis, we find an age-related decline in the numerical density of presumptive inhibitory synapses in layer 2 of the sensorimotor cortex of the Brown Norway x Fisher 344 rat. This age-related decline in presumptive inhibitory synapses is maintained when the density of synapses is combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 51 publications
3
28
1
Order By: Relevance
“…This finding is in agreement with the data of other authors, who reported no significant changes accompanying aging in the total number of neurons in the inferior colliculus, hippocampus or cortex in rats (Helfert et al, 1999;Poe et al, 2001;Merrill et al, 2001;Stanley and Shetty, 2004). In our experiments, the decrease in the optical density of GAD-immunoreactive somas rather suggests the diminished expression of the protein, beyond the level detectable by immunohistochemical methods, as the major reason for the reduced number of GAD-ir…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in agreement with the data of other authors, who reported no significant changes accompanying aging in the total number of neurons in the inferior colliculus, hippocampus or cortex in rats (Helfert et al, 1999;Poe et al, 2001;Merrill et al, 2001;Stanley and Shetty, 2004). In our experiments, the decrease in the optical density of GAD-immunoreactive somas rather suggests the diminished expression of the protein, beyond the level detectable by immunohistochemical methods, as the major reason for the reduced number of GAD-ir…”
Section: Discussionsupporting
confidence: 94%
“…Western blot protein analysis in our experiments showed a statistically less pronounced decline in GAD65 and GAD67 levels with aging in the VC compared to the AC, which may signal different GABA-related aging processes in the two cortical sensory areas. A decreased function of the GABA inhibitory system with aging was also documented in the rat hippocampus (Stanley and Shetty, 2004;Shi et al, 2004;Ling et al, 2005), while no reduction in the number of GABA neurons or GAD immunoreactivity was found in the septum, sensorimotor cortex or parietal cortex (Krzywkovski et al, 1995;Poe et al, 2001;Ling et al, 2005;Shi et al, 2006). Therefore, it is evident that aging is not necessarily accompanied with a homogenous decline of GABA levels in all brain regions.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is in agreement with a paper by Merrill et al (2001), who reported no significant changes in the total number of neurons in the cortex of old F344 rats in comparison with young animals. In addition, also Poe et al (2001) in the rat sensorimotor cortex and Helfert et al(1999) in the rat inferior colliculus did not reported any age-related decline in the total quantity of neurons but rather morphological and synaptic changes. Interestingly, staining for calbindin and calretinin did not reveal any numerical changes in the cortical areas of old F344 rats where PV-ir neurons were absent or…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…However, there is evidence that reduced inhibition developing at high age is associated with decrease of function. For example, a recent ultrastructural study revealed a significant age-related decline in the numerical density of presumptive inhibitory synapses of sensorimotor cortex (Poe et al, 2001), demonstrating a deficit in the intrinsic inhibitory circuitry of the aging neocortex. This observation is in agreement with recent reports where comparison of stimulus selectivity of cells in V1 in young and old macaque monkeys revealed a significant degradation of orientation and direction selectivity in old animals (Schmolesky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%